Crystalline NiFe layered double hydroxide with large pore volume as oxygen evolution electrocatalysts - Long, Junxi; Zhang, Jiaxin; Xu, Xuetang; Wang, Fan (Materials chemistry and physics, 2020)
Cost-effective and earth-abundant electrocatalysts with high activity for oxygen evolution reaction (OER) is essential for achieving efficient and economical electrochemical water splitting. In this work, we developed a facile low-temperature coprecipitation approach to synthesize NiFe layered double hydroxide (NiFe LDH). By tuning Ni/Fe feed ratio and using Na2CO3 as precipitant, mesoporous NiFe LDH nanoparticles were obtained. The special physicochemical features of these NiFe LDH nanoparticles, including high degree of crystallization, large pore volume and abundant crystalline/amorphous interfaces, synergistically endowed the catalyst with enriched active sites. Consequently, the optimal Ni0.66Fe0.33 LDH electrocatalyst showed excellent activity toward OER in alkaline media, with a low overpotential of 248 mV to deliver a current density of 10 mA cm−2, a small Tafel slope of 46 mV dec−1, and strong durability. This work opens an innovative avenue toward the design of advanced NiFe-based catalysts. [Display omitted] •Crystalline NiFe LDH mesostructure prepared by low-temperature precipitation.•Ni0.66Fe0.33 LDH with high pore volume (0.99 cm3 g−1) as electrocatalyst for OER.•Overpotential of 248 mV and Tafel slope of 46 mV·dec−1 are achieved.